The interdependence of ancestors and their descendants. Issue 3 (3rd July 2021) - Clark, Kyle J.; Coe, Kathryn
ABSTRACT: Ancestor worship, the communicated acceptance of the claim that dead ancestors influence and/or are influenced by their living descendants, has been documented in societies all over the world. Despite some researchers' claims that ancestor worship was once universal, there have been relatively few attempts to explain how and why this behavior became so prominent in unrelated and geographically separated societies. A notable exception is the descendant-leaving strategy model that claims ancestor worship is a traditional strategy that had the effect of influencing the behavior of multiple generations of descendants of a common ancestor. This model describes the function of ancestor worship as promoting altruism and cooperation among descendants, even those who are only distantly related. Here we reframe the descendant-leaving strategy theory of ancestor worship in terms of fitness interdependence. In other words, ancestor worship is a descendant-leaving strategy that can explain interesting patterns of fitness interdependence, namely, ancestor-descendant and intergenerational cooperation, which led to the persistence of ancestor worship.